(untitled) (Communications in Inorganic Synthesis, 2016)
Chemistry of 1,1’-bis(ortho-carborane) is rapidly developing during the last years when convenient method of itssynthesis was elaborated. Here we review the recent progress in this field with main imphasis on synthesis of 1,1’-bis(ortho-carborane) based transition metal complexes and heterocycles.